Public and Private Financial Institutions: A Review of Reports from Two Presidential Committees - Meltzer, Allan H. (The Review of Economics and Statistics, 1964)
THEORIES of monetary and financial markets are generally concerned with the behavior of broad aggregates. As yet, economists have not successfully blended the rich variety of institutional details that make up the financial markets with the theory of relative prices. Perhaps as a result of our procedures and the state of knowledge, our policy recommendations are often suggestions for pervasive changes in institutional arrangements. Many of our perennial policy debates are concerned with issues such as whether or not the Federal Reserve should be replaced by an immutable rule or whether banks should be prevented from independently creating money